Char-CO2 reaction behaviour and interactions of coal gangue/weathered coal and coal gangue/pine sawdust blends - Zhang, Yuanyuan; Zhao, Peizhen; Yang, Fengling (Journal of thermal analysis and calorimetry, 2023)
The char-CO 2 reaction behaviour is important for oxy-fuel combustion of coal gangue and weathered coal or biomass. The thermal conversion characteristics of coal gangue, weathered coal, pine sawdust and their blends in CO 2 /N 2 atmosphere were investigated using thermogravimetric analysis, focusing on the reaction behaviour of char and CO 2 . The results showed that the thermal conversion of coal gangue, weathered coal and pine sawdust all had two main stages, but pine sawdust had shorter time of thermal conversion. Mass loss of coal gangue/pine sawdust blends included two obvious stages with four overlapped peaks, which was different from coal gangue/weathered coal mixtures with two separated peaks. The addition of weathered coal or pine sawdust could improve the char-CO 2 reactivity of coal gangue. However, the interactions were absent for all the coal gangue/weathered coal mixtures, and interaction between coal gangue and pine sawdust was obvious during the reaction of char and CO 2 , which was affected by the blending ratio of pine sawdust.